Pengaruh Tingkat Pendidikan, Kompensasi, dan Work-Life Balance terhadap Labor Turnover (Studi pada CV Rinjani) - Awan, Feby Azhar; Jaya, Rama Chandra (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This research examines the influence of education level, compensation and work-life balance on labor turnover at CV Rinjani. This research uses multiple linear regression analysis and involves a population of 50 employees. Labor turnover is the dependent variable, while the independent variables are education level, compensation, and work-life balance. The dimensions of labor turnover encompass intention to quit, job search activities, and contemplating resignation. Educational level is categorized into three dimensions: level of education, alignment with one's major, and competency. The dimensions of compensation consist of financial and non-financial rewards. Work-life balance dimensions include work interference with personal life, personal life interference with work, personal life-enhancing work, and work-enhancing personal life. Data collection was carried out using observation and questionnaires. Various statistical methods, such as partial hypothesis testing, simultaneous analysis, and coefficient of determination, should be used in the study. The research results show that the level of education partially influences labor turnover. Partial compensation does not affect labor turnover. Work-life balance partially influences labor turnover. Education level, compensation, and work-life balance simultaneously influence labor turnover